2015
DOI: 10.1371/journal.pone.0140523
|View full text |Cite
|
Sign up to set email alerts
|

MreC and MreD Proteins Are Not Required for Growth of Staphylococcus aureus

Abstract: The transmembrane proteins MreC and MreD are present in a wide variety of bacteria and are thought to be involved in cell shape determination. Together with the actin homologue MreB and other morphological elements, they play an essential role in the synthesis of the lateral cell wall in rod-shaped bacteria. In ovococcus, which lack MreB homologues, mreCD are also essential and have been implicated in peripheral cell wall synthesis. In this work we addressed the possible roles of MreC and MreD in the spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…An interaction between CozEa and MreC was detected, however, neither CozEa nor CozEb could interact with MreD. Although the CozEa‐MreC interaction may be important for directing peptidoglycan synthesis, like in S. pneumoniae , it is worth noting MreC and MreD are non‐essential in S. aureus (Tavares et al, ). The significance of the CozEa‐MreC interaction thus remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between CozEa and MreC was detected, however, neither CozEa nor CozEb could interact with MreD. Although the CozEa‐MreC interaction may be important for directing peptidoglycan synthesis, like in S. pneumoniae , it is worth noting MreC and MreD are non‐essential in S. aureus (Tavares et al, ). The significance of the CozEa‐MreC interaction thus remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Images were obtained using 5 grid rotations, with 34 m grating period for the 561 nm laser and 23 m period for 405 nm laser. Images were acquired using a sCMOS camera and reconstructed using ZEN software (black edition, 2012, version 8.1.0.484) based on a structured illumination algorithm as previously described (26).…”
Section: Spot Test Assaymentioning
confidence: 99%
“…Interestingly, the shape-determining proteins MreC and MreD proteins are present in this organism and localize to division sites. However, deletion studies indicated that these proteins are not major factors in regulating septal or peripheral peptidoglycan synthesis (127). The homolog of a negative regulator of FtsZ, EzrA, which is conserved among several Gram-positive bacteria (86), directly interacts with FtsZ in S. aureus (122), and localizes to division sites and participates in regulating cell size in S. aureus by controlling peptidoglycan synthesis and cell division (68, 123).…”
Section: Introductionmentioning
confidence: 99%